2014
DOI: 10.1080/11263504.2014.976290
|View full text |Cite
|
Sign up to set email alerts
|

Pollen limitation and fruit abortion in a declining rare tree, the Eurasian yew (Taxus baccataL.): A reproductive cost of ecological marginality

Abstract: Populations of rare tree species such as the dioecious and anemophilous yew (Taxus baccata) are especially prone to extinction if they occupy marginal habitats. This is the case of yew populations growing in Mediterranean mountains under dry climate and a severe anthropogenic disturbance regime, which show insufficient regeneration. We examined two of the likely mechanisms driving this population decline. The study was conducted in a central Spanish yew population in 2005 and 2006.On one hand, we tested for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…This mechanism is, however, strongly context‐dependent being selectively advantageous when populations are small and/or exposed to higher rates of turnover which partly mimics situation after long‐distance dispersal (Pannell et al., 2015). Indeed, the number of compatible mates and their density are critical factors for successful establishment and maintenance of populations at range margins (Rasmussen & Kollmann, 2004, Elam et al 2007, Kanarek et al., 2013, Sanz & Pulido, 2015, Hamston et al., 2017). Because the regions solely occupied by H. alpinum apomicts, that is the Alps, Scandinavia and in a lesser extent also the Western Carpathians, were under a much stronger influence of Quaternary glaciation cycles when compared to southerly situated the South‐eastern Carpathians occupied by sexuals (Mráz & Ronikier, 2016), we could expect more intense metapopulation dynamics of fragmented and small‐sized populations during the post‐glacial recolonization of formerly glaciated regions.…”
Section: Resultsmentioning
confidence: 99%
“…This mechanism is, however, strongly context‐dependent being selectively advantageous when populations are small and/or exposed to higher rates of turnover which partly mimics situation after long‐distance dispersal (Pannell et al., 2015). Indeed, the number of compatible mates and their density are critical factors for successful establishment and maintenance of populations at range margins (Rasmussen & Kollmann, 2004, Elam et al 2007, Kanarek et al., 2013, Sanz & Pulido, 2015, Hamston et al., 2017). Because the regions solely occupied by H. alpinum apomicts, that is the Alps, Scandinavia and in a lesser extent also the Western Carpathians, were under a much stronger influence of Quaternary glaciation cycles when compared to southerly situated the South‐eastern Carpathians occupied by sexuals (Mráz & Ronikier, 2016), we could expect more intense metapopulation dynamics of fragmented and small‐sized populations during the post‐glacial recolonization of formerly glaciated regions.…”
Section: Resultsmentioning
confidence: 99%
“…Taking this into consideration, we kept plants in the same environmental conditions and kept female plants close to male plants (in a 1:1 ratio) to ensure a high probability of pollination and fertilisation. This suggests that, although in a rich environment, female plants invest more into production of numerous flowers, while the efficiency of seed development and seed production is related to factors other than just nutritional availability and pollen availability [ 47 ]. Moreover, our earlier studies showed that fertilised female plants of both species are characterised by higher photosynthetic activity [ 38 , 48 ] and higher biomass [ 39 ] than their non-fertilised counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our earlier studies showed that fertilised female plants of both species are characterised by higher photosynthetic activity [ 38 , 48 ] and higher biomass [ 39 ] than their non-fertilised counterparts. These observations indicate that the allocation of plant resources to seed production is a reasonable/controlled investment of resource allocation; thus, in a non-fertilised environment, when the plant has already invested part of the available resource for female reproductive structure development, the necessary resources were provided by the plant (at the cost of vegetative growth or resource allocation) to ensure development of seeds [ 47 ]. All of the above suggests that plants have evolved mechanisms of compensation of cost of reproduction, and this mechanism can be switched on after flower production but before embryo/seed development, and results in abortion of female reproductive structures just shortly before or after ovule fertilisation.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, considering the ongoing climate changes and the fact that harsh climatic conditions near the southern range limit already affect populations of T. baccata (Sanz et al 2009, Linares 2013, Sanz and Pulido 2014), conservation of this species within its entire natural distribution is important in order to protect the species under future conditions. Although environmental conditions in the northern part of the T. baccata range are expected to remain or become more favorable for T. baccata survival in the future, natural spread of the species is slow (Svenning and Magård 1999).…”
Section: Discussionmentioning
confidence: 99%